HUBUNGAN KUALITAS PELAYANAN KEPERAWATAN DENGAN KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT - Septi Darmayanti; Nani Asna Dewi; Nur Endah R.; Sofie Handajany (Institut Kesehatan Hermina, 2024)
Hospitals are health service providers whose main role is providing care and attention to patients, carrying out health activities by healing and restoring health. Good service quality arises from the perception of patients who expect the service they receive to be in line with expectations. Patient satisfaction in hospitals is influenced by many things, including the availability of complete medical equipment, strategically located buildings, good hospital equipment, provision of facilities and infrastructure for services. Research Objective: To determine the relationship between the quality of nursing services and patient satisfaction at the Hermina Hospital inpatient setting. Research Method: Quantitative research type with correlation research type with a cross sectional approach. The research population was all patients who received nursing services in the Hermina Hospital inpatient room, totaling 104 people using purposive sampling technique. The data collection instrument uses a questionnaire. Statistical analysis used Chi-Square (X2). Research Results: Chi-Square statistical test using SPSS 25 obtained normal data of 0 cells, 25%, meaning the chi-Square test meets the requirements, then the Pearson chi-square value has a significance level of 95%, indicating that the probability value is 0.000 (p<0, 05), meaning Ho is rejected and Ha is accepted. The conclusion is that there is a relationship between the quality of nursing services and patient satisfaction at the Inpatient Hospital of Hermina Metland Cibitung, Galaxy, Periuk Tangerang and Karawang